Hidrosefalus Pada Anak - Apriyanto .; Rhonaz Putra Agung; Fadillah Sari (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
ABSTRACT Hydrocephalus is a common clinical problem found in pediatric neurosurgical practice. This condition involves dilatation of cerebral ventricular system due to various etiologies. It is classified into two conditions, communicative and obstruction type. Various etiologies cause different clinical features and need different modality of treatments. Ventriculoperitoneal shunt is the gold standard of treatment, but Endoscopic 3rd ventriculostomy is considered as a treatment of choice nowadays. This article concerns all aspect of this condition: epidemiology, etiology, pathophysiology, simptoms and clinical findings, treatment, and prognosis. Key words: Hydocephalus in Pediatric, neurosurgery, VP Shunt, Endoscopic 3rd , ventriculostomy.